2007
DOI: 10.1161/circulationaha.107.185650
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Public Health in Older Adults

Abstract: Objective-To issue a recommendation on the types and amounts of physical activity needed to improve and maintain health in older adults. Participants-A panel of scientists with expertise in public health, behavioral science, epidemiology, exercise science, medicine, and gerontology. Evidence-The expert panel reviewed existing consensus statements and relevant evidence from primary research articles and reviews of the literature. Process: After drafting a recommendation for the older adult population and review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
472
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,668 publications
(499 citation statements)
references
References 65 publications
(35 reference statements)
17
472
1
9
Order By: Relevance
“…A classificação dos idosos em ativos e não ativos baseou-se nas recomendações do American College of Sports Medicine e da American Heart Association, que classificam como ativos os indivíduos que praticam até 150 minutos por semana de atividade física de intensidade no mínimo moderada [12]. A classificação do grau de atividade física foi feita pela análise dos dados coletados na ficha de avaliação dos sujeitos.…”
Section: Métodosunclassified
“…A classificação dos idosos em ativos e não ativos baseou-se nas recomendações do American College of Sports Medicine e da American Heart Association, que classificam como ativos os indivíduos que praticam até 150 minutos por semana de atividade física de intensidade no mínimo moderada [12]. A classificação do grau de atividade física foi feita pela análise dos dados coletados na ficha de avaliação dos sujeitos.…”
Section: Métodosunclassified
“…It is recommended to use (lower limb) resistance training according to ACSM (two or three times a week) ("ACSM", 1998a; "ACSM", 1998b; Garber et al, 2011). Exercises should be performed at 60-80% of the first repetition maximum (RM), resistance exercises should train 8-10 exercises involving the major muscle groups in bouts of 8-15 repetitions at least 30 minutes a day of moderate-intensity activity on two or three non-consecutive days each week (Nelson et al, 2007). Multiple sets of repetitions (2-5 sets) provide greater benefit (Langer et al, 2009).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Engaging in moderate-to-vigorous physical activity (e.g., walking and cycling) for 30 minutes 5 days per week significantly reduces the age-related risk of diseases in older adults 4,5) . One review study has shown cycling significantly reduces risk for all-cause and cancer mortality 6) , and improves cardiovascular risk factors 6) .…”
Section: Introductionmentioning
confidence: 99%